Precauções padrão e específicas para controle da transmissão de patógenos: necessidades na atenção primária em saúde - Maroldi, Michely Aparecida Cardoso (2015)
The adherence of health workers to universal precautions (UP) and specific precautions (SP) is essential to prevent the transmission of microorganisms. The literature contains few studies about adherence to these precautions outside the hospital environment, particularly in primary health care (PHC). With the increased incidence of patients colonized with multidrug-resistant germs and high prevalence of tuberculosis (TB) in the country, increased the need for research on the transmission of microorganism sat this level of attention. This study aimed to identify, together with the PHC professionals, the know ledge needs of UP and SP as well as elements that may interfere with adherence to these measures. This is a qualitative study, which were conducted four focus groups and three interviews with health professionals in the city of São Carlos / SP and Itirapina / SP. This study was approved by the Research Ethics Committee. The content of groups and interviews were transcribed and analyzed under the premises of qualitative research, the following themes were identified: lack of knowledge about activities that require protection; difficulties with infrastructure; quality and availability of materials; behavioral problems; need for training; and other issues. Professionals acknowledged the difficulties in the face of infection related to assistance to health (IRAH) and the adoption of basic measures for their control, and the need for more training and expanding the capabilities approach for the multidisciplinary team. Thus, this study brings expertise on the subject in the PHC contributing to the elaboration of recommendation sand guides new educational actions to minimize the risk of transmission of infection, in addition to supporting the development of new research in this area of attention.